Tactical behavior of U-15 soccer players: assessment of changes over a season - Gibson Moreira Praça; Raphael Brito e Sousa; Jorge Victor de Oliveira Silva; Frederico Gonçalves Constantino; Pedro Emílio Drumond Moreira; Igor Junio de Oliveira Custódio; Juan Carlos Pérez Morales; Pablo Juan Greco (Universidade Federal de Santa Catarina, 2017)
This study aimed to compare the tactical behavior of U-15 soccer players over a season. Sixteen high-level athletes (mean age 14.5 years) from the city of Belo Horizonte participated in the study. Athletes were monthly evaluated by means of the field test using the System of Tactical Assessment in Soccer - FUTSAT, which allowed the characterization of the incidence of tactical principles and place of action in the game field, as well as the percentage of positive offensive and defensive tactical principles. Data were analyzed by Friedman's test (incidence of tactical principles and place of the action) and one-way ANOVA for repeated measures (percentage of positive tactical principles), adopting significance level of p<0.05. Results showed differences in the incidence of offensive and defensive units tactical principle, as well as the place of actions in the game field. An improvement in offensive and defensive tactical behavior was also observed throughout the season.